(untitled) (Malaysian Management Journal, 2010)
This paper describes a new model developed for make-to-order (MTO) sectors namely SHEN Principles, which aims to fill a gap in the world-class manufacturing (WCM) literature that concentrates on the characteristics of the larger traditional make-to-stock (MTS) sector. Using evidence from the literature, especially the MTO literature and the more comprehensive WCM models, a new model was devised. This was then modified in the light of case study evidence collected from the six MTO companies ranging from small-to medium-sized MTO companies. The model presented in this paper known as â€œSHEN Principleâ€, will be the current version of the model after all the modifications have been incorporated.